1987
DOI: 10.1016/0378-5955(87)90061-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isolated outer hair cells from five mammalian species

Abstract: Live outer hair cells were isolated from guinea pig, chinchilla, rat, mouse, and gerbil. The organ of Corti from selected turns of the cochlea was briefly incubated with collagenase and outer hair cells were separated from the tissue by micromanipulation under microscopic observation.Morphological criteria for cell viability were: (1) cylindrical cell shape without swelling or distortion of the membrane;(2) location of the nucleus in its normal position near the base of the cell; (3) cytoplasm devoid of Browni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…In order to differentiate basal and apical outer hair cells, the 2 first turns (from the base of the cochlea) and the 2 apical turns of the organ of Corti were collected and sampled separately. These were kept at room temperature (20-22°C) in Hank's Balanced Salt Solution (HBSS: 137 rnM-NaCl, 5.4 mM KCl, 1.25 mM CaCl,, 0.5 mM MgCl,, 0.4 mM MgSO,, 0.33 mM Na,HPO,, 0.44 mM KH,PO,, 5.5 mM D-glucose; Gibco Laboratories, Grand Island, NY) buffered to pH 7.4 with 5 mM sodium HEPES (Dulon et al, 1987;Zajic and Schacht, 1987). After a lo-min incubation with 0.5 mg collagenase (type IV, Sigma, St, Louis, MO) per ml HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…In order to differentiate basal and apical outer hair cells, the 2 first turns (from the base of the cochlea) and the 2 apical turns of the organ of Corti were collected and sampled separately. These were kept at room temperature (20-22°C) in Hank's Balanced Salt Solution (HBSS: 137 rnM-NaCl, 5.4 mM KCl, 1.25 mM CaCl,, 0.5 mM MgCl,, 0.4 mM MgSO,, 0.33 mM Na,HPO,, 0.44 mM KH,PO,, 5.5 mM D-glucose; Gibco Laboratories, Grand Island, NY) buffered to pH 7.4 with 5 mM sodium HEPES (Dulon et al, 1987;Zajic and Schacht, 1987). After a lo-min incubation with 0.5 mg collagenase (type IV, Sigma, St, Louis, MO) per ml HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…The coils were gently transferred with a 70 Al volume of MEM to a perfusion chamber. This procedure usually yielded a large number of healthy isolated outer hair cells (Zajic and Schacht, 1987). The outer hair cells retained their normal morphology for an average time of 4 h. Stable currents could be usually recorded from such outer hair cells for more than 1 h when perfused with control solutions, drug-containing solutions, followed by control solutions for washout.…”
Section: Methodsmentioning
confidence: 99%
“…Mammalian OHCs are slender cylindrical structures with fairly uniform diameters (8-10 mm), and with lengths ranging from 20-30 mm in the high-frequency cochlear base to approximately about 80-100 mm in the lowfrequency apex (Dallos et al, 1991). Zajic and Schacht (1987) isolated OHCs from guinea pigs, chinchillas, rats, mice, and gerbils. They found that the morphological features of these OHCs were similar and that the cells were cylindrical.…”
Section: Discussionmentioning
confidence: 99%